Fixed Point Results in Orthogonal Neutrosophic Metric Spaces. (9th August 2021) - Ishtiaq, Umar; Javed, Khalil; Uddin, Fahim; Sen, Manuel de la; Ahmed, Khalil; Ali, Muhammad Usman
Abstract : Neutrosophy deals with neutrosophic logic, probability, and sets. Actually, the neutrosophic set is a generalization of the classical set, fuzzy set, and intuitionistic fuzzy set. A neutrosophic set is a mathematical notion serving issues containing inconsistent, indeterminate, and imprecise data. The notion of intuitionistic fuzzy metric space is useful in modelling some phenomena, where it is necessary to study the relationship between two probability functions. In this study, the concept of an orthogonal neutrosophic metric space is initiated. It is a generalization of the neutrosophic metric space. Some fixed point results are investigated in this setting. For the validity of the obtained results, some nontrivial examples are given.